CLINICAL FEATURES OF COMBINATION OF MYOCARDIAL INFARCTION AND ACUTE STROKE (Archive of Conferences, 2020)
Cardiovascular and cerebrovascular diseases are the most pressing medical and social problems in the world. The increase in the prevalence of vascular diseases, which has been noted in recent years, has led to an increase in the incidence of acute myocardial infarction and cerebrovascular accident. Men suffer from ischemic heart disease much more often than women. At the age of 40-60, myocardial infarction is 3-5 times more common in men due to the earlier (10 years earlier than in women) development of atherosclerosis